Pengaruh Harga dan Citra Merek terhadap Loyalitas Merek PT. Andalas Nusa Perkasa Medan - Daniel Christian; Thomas Sumarsan Goh; Errie Margery; Syawaluddin Syawaluddin (YUME : Journal of Management, 2021)
AbstractThis research was conducted on consumers who work at PT. Andalas Nusa Perkasa Medan. The purpose of this study was to determine and analyze the effect of price and brand image on brand loyalty. The population and sample in this study amounted to 58 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously price and brand image have a positive and significant effect on brand loyalty PT. Andalas Nusa Perkasa Medan. Partially, the price has a positive and significant effect on brand loyalty PT. Andalas Nusa Perkasa Medan. Partially, brand image has a positive and significant effect on brand loyalty of PT. Andalas Nusa Perkasa Medan. The magnitude of the coefficient of determination can be seen from the RSquare value of 0.223 which means that price and brand image can explain brand loyalty by 22.3% while the remaining 77.7% is influenced by variables not examined such as: product design, distribution channels, and so on. Keywords: Price, Brand Image, Brand Loyalty.